Enhancing academic credential integrity through blockchain-based verification systems - Awang Abu Bakar, Normi Sham; Yahya, Norzariyah; Idris, Norbik Bashah; Mohd Nordin, Mohd Asyraf; Zakaria, Zayani (IOS Press, 2025)
The emergence of forged engineering degrees submitted to the Board of Engineers Malaysia, fake diplomas issued by a former college CEO, and online syndicates selling counterfeit academic credentials for RM1,500 to RM4,000 clearly demonstrates the failure of current institutional controls and emphasizes the urgent need for a secure and unified verification system. This paper examines the potential of blockchain technology as a transformative solution for academic certificate verification. This aligns with Malaysia’s National EdTech Policy and the 2018 rollout of the blockchain-based eScroll by the Ministry of Higher Education and six public universities, as well as broader national strategies including MyDIGITAL under the 4IR Blueprint and Malaysia Blockchain Infrastructure. The study reviews current implementations and research on blockchain-based systems, including case studies such as CredChain, EduTrust, and UTM-BADVES, which demonstrate practical viability and enhanced security. A detailed examination of the eScroll system, developed by the International Islamic University Malaysia (IIUM), provides insights into a localized application of blockchain for academic credentialing. The eScroll system utilizes a permissioned blockchain, enabling only authorized institution, such as accredited universities and regulatory bodies to access, verify, and update academic credentials securely and transparently. To ensure data integrity and tamper-resistance, the system employs cryptographic hash functions such as SHA-256, which generate unique, immutable digital fingerprints of each credential. While the technology presents clear advantages, including fraud prevention, real-time validation, and cost reduction, challenges remain in terms of scalability, regulatory compliance, and interoperability. The paper concludes by emphasizing the need for strategic institutional adoption, standardized frameworks, and cross-sector collaboration to fully realize the benefits of blockchain in securing Malaysia’s educational ecosystem. Future work include, integration with the Malaysian Qualifications Agency (MQA) databases would allow real-time synchronization and validation of program accreditations and graduate information, enhancing regulatory oversight and ensuring consistency with nationally recognized qualification frameworks. To further enhance adoption and practical utility, blockchain-based credentialing systems such as eScroll can benefit from strategic partnerships with professional networking platforms like LinkedIn and major job portals.